2014
DOI: 10.1007/s00402-014-1973-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of non-union of humerus diaphyseal fractures: a prospective study comparing interlocking nail and locking compression plate

Abstract: This study concludes that both the implants can be used in non-union of humeral shaft fractures with good functional outcomes and acceptable rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…These studies may have contained a selection bias, that is, simple fractures tend to be managed conservatively and more complicated fractures, operatively. The causes of humeral shaft nonunion include infection, distraction at the fracture site, soft tissue interposition, unstable fixation, and wrong choice of implant [2]. In terms of factors that inhibit fracture healing, smoking, diabetes, medications, malnutrition, and noncompliance with physicians' instructions have been implicated [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies may have contained a selection bias, that is, simple fractures tend to be managed conservatively and more complicated fractures, operatively. The causes of humeral shaft nonunion include infection, distraction at the fracture site, soft tissue interposition, unstable fixation, and wrong choice of implant [2]. In terms of factors that inhibit fracture healing, smoking, diabetes, medications, malnutrition, and noncompliance with physicians' instructions have been implicated [13].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that plate fixation with autologous bone grafting is the best treatment for humeral shaft nonunion, and they did not recommend IMN because of the lower union rates. It has been suggested that IMN has lower bone union rates because of a lack of compression force on the fracture site and poor rotational stability [2,16]. Augmentative plating with nail retention also can be a choice of treatment for humeral shaft nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of rigid plate fixation and iliac crest autograft results in a high success rate for aseptic non-union of the humeral shaft when no large defects are present [3,4,9,12,15,17,18,20,21,32,[34][35][36]. The inherent biomechanics of the humeral shaft can explain why intramedullary (IM) nailing is not as successful as in the lower limb [1,2,7,13,19,28,34]. Persistent non-union can be defined as known failure of at least one surgical attempt at bone union in a confirmed case of nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Singh AK and colleagues [1] have done an interesting study in the treatment of non-union of humerus diaphyseal fractures through comparing of interlocking nail and locking compression plate, which found both the implants can be used in non-union of humeral shaft fractures with good functional outcomes and acceptable rate of complications. However, we have some concerns regarding the paper and wish to share them.…”
mentioning
confidence: 99%